Pemanfaatan Rebusan Krokot (Portulaca oleracea L.) sebagai Fitonutrien Alami untuk Meningkatkan Kualitas Daging Ayam Broiler - Mulik, Simon Edison; Ndun, Alberth Nugrahadi; Nguru, David Agustinus (Jurnal Ilmiah Inovasi, 2026)
Purslane is a plant that contains antioxidants and phenolic compounds that can be used to produce the best quality meat without causing negative effects for consumers. The purpose of this study is to determine the physical quality of broiler chicken meat after the administration of purslane stew in drinking water. This study used a completely randomized design with 4 treatments and 5 replications. The treatment in this study consisted of Pr0 (control, without being given purslane decoction in drinking water), Pr1 (25 mL of decoction/liter of drinking water), Pr2 (50 mL of decoction/liter of drinking water), and Pr3 (75 mL of decoction/liter of drinking water). The parameters studied were pH, water holding capacity, and cooking loss. The data obtained were analyzed using analysis of variance. Based on the results of the study, it is known that the administration of purslane decoction in drinking water with different levels produces higher water holding capacity compared with control (P<0,05), on the other hand, the cooking loss has decreased (P<0,05). There were no effect of treatments (P>0,05) on meat pH. It was concluded that the administration of purslane decoction up to the level of 75 mL/liter in drinking water produced a relatively similar meat pH, increased water holding capacity, and decreased the cooking loss